2016
DOI: 10.3346/jkms.2016.31.1.18
|View full text |Cite
|
Sign up to set email alerts
|

Allergenic Characterization of 27-kDa Glycoprotein, a Novel Heat Stable Allergen, from the Pupa of Silkworm, Bombyx mori

Abstract: Boiled silkworm pupa is a traditional food in Asia, and patients with silkworm pupa food allergy are common in these regions. Still now only one allergen from silkworm, arginine kinase, has been identified. The purpose of this study was to identify novel food allergens in silkworm pupa by analyzing a protein extract after heat treatment. Heat treated extracts were examined by proteomic analysis. A 27-kDa glycoprotein was identified, expressed in Escherichia coli, and purified. IgE reactivity of the recombinant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 22 publications
0
28
0
Order By: Relevance
“…Of these 25 articles, 8 studied the cross-reactivity/cosensitisation between edible insects, crustaceans and HDM [35][36][37][38][39][40][41][42], 3 identified and characterized allergens of edible insects [43][44][45], 10 were cases reports or case series of food allergy caused by insects (8 case reports [46][47][48][49][50][51][52][53], and 2 case series [54,55]), 3 assessed the frequency of anaphylaxis caused by entomophagy [56][57][58] and 1 assessed the prevalence of allergy among insect-eaters [59].…”
Section: Resultsmentioning
confidence: 99%
“…Of these 25 articles, 8 studied the cross-reactivity/cosensitisation between edible insects, crustaceans and HDM [35][36][37][38][39][40][41][42], 3 identified and characterized allergens of edible insects [43][44][45], 10 were cases reports or case series of food allergy caused by insects (8 case reports [46][47][48][49][50][51][52][53], and 2 case series [54,55]), 3 assessed the frequency of anaphylaxis caused by entomophagy [56][57][58] and 1 assessed the prevalence of allergy among insect-eaters [59].…”
Section: Resultsmentioning
confidence: 99%
“…Notably, of the 36 proteins identified in the present study, the mRNA and protein expression of Jafrac1, p27k, arginine kinase, and paramyosin, which are the four known allergens, were significantly downregulated. Studies have shown that the four proteins can induce an IgE‐mediated allergic response in patients (García‐Orozco, Aispuro‐Hernández, Yepiz‐Plascencia, Calderón‐de‐la‐Barca, & Sotelo‐Mundo, ; Jeong et al, ; H. Wang et al, ; Zhao, Li, Kuang, Luo, & Li, ). Moreover, p27k and arginine kinase are thermostable, and thus, their allergenicity cannot be destroyed by heating (García‐Orozco et al, ; Jeong et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the four proteins can induce an IgE‐mediated allergic response in patients (García‐Orozco, Aispuro‐Hernández, Yepiz‐Plascencia, Calderón‐de‐la‐Barca, & Sotelo‐Mundo, ; Jeong et al, ; H. Wang et al, ; Zhao, Li, Kuang, Luo, & Li, ). Moreover, p27k and arginine kinase are thermostable, and thus, their allergenicity cannot be destroyed by heating (García‐Orozco et al, ; Jeong et al, ). Madero et al () showed that the 27‐kDa hemolymph protein of Galleria mellonella , an airborne allergen, shares 54.9% amino acid similarity with p27k of the silkworm, further highlighting its allergenicity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations